Optimum maintenance strategy for deteriorating bridge structures based on lifetime functions - Yang, Seung-Ie (2006)
The highway networks of most European and North American countries are completed or close to completion. However, many of their bridges are aging, and in the United States alone a very significant part of the about 600,000 existing bridges is considered to be deficient and must be replaced, repaired or upgraded in the short term. The funds available for the maintenance of existing highway bridges are extremely limited when compared with the huge investment necessary, and must, therefore, be spent wisely. In this paper, a model based on lifetime functions for predicting the evolution in time of the reliability of deteriorating bridges under maintenance is presented. This model uses the probability of satisfactory system performance during a specified time interval as a measure of reliability and treats each bridge structure as a system composed of several components. In this manner, it is possible to predict the structural performance of deteriorating structures in a probabilistic framework. In addition, the optimum maintenance strategy is identified using as objective the minimization of the present value of the life-cycle maintenance cost. An existing bridge is analyzed using lifetime functions and its optimum maintenance strategy is found.